2011
DOI: 10.1021/pr200021n
|View full text |Cite
|
Sign up to set email alerts
|

Biospecimen Reporting for Improved Study Quality (BRISQ)

Abstract: Human biospecimens are subject to a number of different collection, processing, and storage factors that can significantly alter their molecular composition and consistency. These biospecimen preanalytical factors, in turn, influence experimental outcomes and the ability to reproduce scientific results. Currently, the extent and type of information specific to the biospecimen preanalytical conditions reported in scientific publications and regulatory submissions varies widely. To improve the quality of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(119 citation statements)
references
References 82 publications
0
116
0
3
Order By: Relevance
“…The biobanking protocol according to Biospecimen Reporting for Improved Study Quality (BRISQ) is as follows [31]. Blood collection for the CVA Biobank is performed according to the biobank SOP.…”
Section: Quality Assurance Measuresmentioning
confidence: 99%
“…The biobanking protocol according to Biospecimen Reporting for Improved Study Quality (BRISQ) is as follows [31]. Blood collection for the CVA Biobank is performed according to the biobank SOP.…”
Section: Quality Assurance Measuresmentioning
confidence: 99%
“…Thus processing conditions that are optimal for one assay are not the same for another, necessitating careful documentation of preanalytical information and harmonization of the methods to document these conditions. The BRISQ (Biospecimen Reporting for Improved Study Quality) guidelines 27 were developed in collaboration with the NCI Biospecimen Research Network to document where biospecimens came from and how they were treated. The guidelines list critical data elements that include general information for consistent documentation of categories of biospecimens and factors that might influence the integrity, quality, and/or molecular composition of biospecimens.…”
Section: Biospecimen Sciencementioning
confidence: 99%
“…The EDRN brings together investigators from discovery laboratories, clinicians and biostatisticians to discuss issues related to clinical needs and study design and to share resources, such as high quality biospecimens that are collected to address a specific clinical question. An NCI workshop sponsored, Development of Biospecimen Reporting Criteria for Publication , concluded that “human biospecimens are subject to a number of different collection, processing, and storage factors that can significantly alter their molecular composition and consistency” and recommended guidelines for reporting data elements for human biospecimens used in biomedical studies, the Biospecimen Reporting for Improved Study Quality (BRISQ) 13 . These reporting guidelines are intended to allow other researchers to better evaluate and reproduce experimental results.…”
Section: It Takes a Village…mentioning
confidence: 99%
“…Investigators EDRN at the DMCC have developed a study design for phase 2/3 biomarker validation trials 13 . They have termed this the PRoBE design for Prospectivespecimen- collection-Retrospective-Blinded-Evaluation.…”
Section: It Takes a Village…mentioning
confidence: 99%